Alcohol and the Medical Community$ba Cocktail for Exclusion - Ellythy, Luqman M. (The Hastings Center report, 2024)
Alcohol is a class 1 carcinogen, and its use, at any level, is not safe for health. Despite this, alcohol remains strongly mixed into medical culture and is often served free at medical-community events. This presents numerous ethical concerns. First, the funding of alcohol-centered events by the medical community reinforces alcohol consumption as a coping mechanism for stress, perpetuates the perceived need for alcohol for socialization, and falsely implies that it is a safe substance. Additionally, the medical community is increasingly diverse, including Muslims, Mormons, those in recovery from substance use disorders, pregnant individuals, and individuals from homes and communities damaged by alcohol. Due to their moral or safety concerns, these individuals may miss opportunities to network and engage in professional development when alcohol is present. Therefore, alcohol acts as a barrier to diversity, equity, and inclusion efforts and can result in pernicious downstream effects for minority patient populations.